The impact of COVID-19 pandemic on diet and lifestyle of undergraduate medical students of South India-a cross sectional study - Shanbhag, Deepthi N.; Shaj, Dana Mariyam; Sheela Justus, Manju Mariya; Sushil, Ann Mary (International Journal of Research in Medical Sciences, 2024)
Background: COVID-19, infectious disease caused by the Corona virus, caused economic and social disruptions all over the World. In order to contain this pandemic, complete/partial lock down was declared in different parts and thus restricting all human activities. Lifestyle behaviours, especially eating habits, physical activity and sleep patterns changed causing complications such as obesity, diabetes and cardiovascular disorders. The prevalence of depression, anxiety and stress increased among the public. Methods: The study is conducted among medical students to find out the extent of after effects of COVID pandemic on the diet and life style of medical students. Online questionnaire was used to access the lifestyle and exercise patterns of medical students across South India. Results: The study reveals that the pandemic has led to notable shifts in the daily routines, eating habits, and overall well-being of this demographic. Factors such as increased stress, remote learning, and limited social interactions have played a crucial role in these changes. Significant change in hours of sleep, and change in sitting and screen time has been observed. Slight increase in the daily intake of fruits and vegetables, intake of balanced diet and immunity-boosting food, consumption of junk food/fast food and fried food has been observed. The consumption of unhealthy food when bored or stressed is also slightly increased. There is also slight change in quality of sleep and participation in exercise. Conclusions: The publication provides insights into the challenges faced by medical students and highlights the importance of addressing these issues to support their health and well-being during these unprecedented times.